Mixture of Salix Genotypes Promotes Root Colonization With Dark Septate Endophytes and Changes P Cycling in the Mycorrhizosphere - Baum, Christel; Hrynkiewicz, Katarzyna; Szymańska, Sonia; Vitow, Nora; Hoeber, Stefanie; Fransson, Petra M. A.; Weih, Martin (Frontiers in Microbiology, 2018)
The roots of Salix spp. can be colonised by two types of mycorrhizal fungi (ectomycorrhizal and arbuscular) and furthermore by dark-septate endophytes. Salix spp. can be dual mycorrhizal (ectomycorrhizal and arbuscular mycorrhizal) and furthermore colonized by dark-septate endophytes. The fungal root colonization is affected by the plant genotype, soil properties and their interactions. However, the impact of host diversity accomplished by mixing different Salix genotypes within the site on root-associated fungi and P-mobilization in the field is not known. It can be hypothesized that mixing of genotypes with strong eco-physiological differences changes the diversity and abundance of root-associated fungi and P-mobilization in the mycorrhizosphere based on different root characteristics. Therefore, we have studied the mixture of two fundamentally eco-physiologically different Salix genotypes (S. dasyclados cv. ‘Loden’ and S. schwerinii × S. viminalis cv. ‘Tora’) compared to plots with pure genotypes in a randomized block design in a field experiment in Northern Germany. We assessed the abundance of mycorrhizal colonization, fungal diversity, fine root density in the soil and activities of hydrolytic enzymes involved in P-mobilization in the mycorrhizosphere in autumn and following spring after three vegetation periods. Mycorrhizal and endophytic diversity was generally low under all Salix treatments with Laccaria tortilis being the dominating ectomyorrhizal fungal species, and Cadophora and Paraphaeosphaeria spp. being the most common endophytic fungi. Interspecific root competition promoted richness and root colonization by endophytic fungi (4 taxa in the mixture vs. one found in the pure host genotype cultures) as well as spore formation of arbuscular fungi more than ectomycorrhizal fungi and increased the activities of hydrolytic soil enzymes involved in the P-mineralization (acid phosphatase and ß-glucosidase) in mixed stands. The data suggest selective promotion of endophytic root colonization and changed competition for nutrients by mixture of Salix genotypes.